Near infrared spectroscopy (NIT) analysis of maize hybrids starch content - Kiss, Csongor (Acta Agraria Debreceniensis, 2013)
The purpose of my research is to find the most favourable maize hybrids for bioethanol-production feedstock, using the so called „NIT”, near infrared spectroscopy method in the analysis of the inner contents especially of starch content. The other goal of my analysis is to reflect on how the effects of the most important growing factors – such as irrigation and the use of different dose fertilizers – contribute to the maize hybrids starch content.